Kisvállalkozások egy iparvárosban (Szociológiai Szemle, 2024)
In the present paper I have attempted to present the density and structure of enterprises in the context o f the local economic structure. I wished to find out what effects shape the sphere of small entrepreneurs in the region and what is the relationship between small enterprise and the region. I was trying to find those, often contradictory, factors, or their constellations, characterising the region and the local economic structure, which may influence the territorial differences in the number and structure of enterprises. Based on international and domestic literature, such factors are, for instance:- the level of development of the (local) economy (West-East slope),- growth of consumption,- technical changes,- unemployment,- the role of foreign capital,- structure of branches,- the structure of companies by size,- local politics, etc.In the case of Győr, a city where the GDP is the highest, next to Budapest, where unemployment is low, and where apparently the crisis of transformation has been accompanied by less jerks, it is all the more interesting that the number of enterprises is not outstanding and it is not above the average of county seats. Small enterprise is characterised by personal services producing for the local market, catering, further on, expedition and building industry, linked to boom. Small enterprise was unable to join the branches of manufacturing and processing industries, and engineering industry first and foremost, dominating the economic structure of the city, hence the proportion of outside small entrepreneurs contributing to them is rather low.Looking for the causes, I studied on the example of Győr, what is the relationship of the density and composition of small enterprise of a town with its structural conditions, and what is the relationship of small enterprises among themselves and to the local economy.